Without reasons ; Disabled not unable ; Ang Bohemya [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
Investigates the murder of three teenage boys. Tackles disabled people from the respected members of society. Rolando Tinio translating La Boheme and adapting it to stage setting.